Comparison of Fuzzy Time Series and Double Smoothing Holt Methods for Rainfall Forecasting - Endang Habinuddin; Euis Sartika; Neneng Nuryati (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
This research aims to compare the time series forecasting method, namely the Fuzzy Time Series method, with Double Exponential Smoothing Holt. The data used in this study is the rainfall data of the city of Bandung every month from January 2012 to December 2021. The analysis of the two methods is seen for accuracy according to the measure of error, namely MSE (Mean Square Error) and MAD (Mean Absolute Deviation). The results show that the Fuzzy Time Series method has MSE of 15558.89 and MAD of 108.97. While the Doube Smoothing Holt method has MSE of 23367.79 and MA of 115.94 So the Fuzzy Time Series method is reliable to use for forecasting rainfall in Bandung because the error values is lower than that of the Exponential Smoothing Holt.